Older women's perceptions of the impact of homelessness on their health needs and their ability to access healthcare. (28th October 2021) - Sutherland, Gloria; Bulsara, Caroline; Robinson, Suzanne; Codde, Jim
Abstract: Objective : This study explored the healthcare needs and barriers to health services in older homeless women in the Perth metropolitan area, Western Australia. Methods : Twenty‐two older women experiencing homelessness completed a questionnaire and semi‐structured interview. Data were analysed using descriptive statistics and thematic analysis. Results : The study highlighted that these women had complex and inter‐related issues that affected their health. The nine major themes that emerged from the interview data consisted of: safe accommodation; financial insecurity; experience of trauma and abuse; stigma, embarrassment and fear of being judged; the health impact of not fulfilling their role as family nurturer; mental health; complex interaction of physical and mental health issues; healthcare costs; and the need for ongoing psychosocial and healthcare support once housed. Conclusion : Provision of safe and secure accommodation is pivotal to women's health, as is the need for greater understanding of the impact of poverty, women's traditional roles, social disconnection and domestic violence, and ongoing access to healthcare and support services. Implications for public health : A structural and systemic approach based on a social determinants of health framework is required to address the health needs of the increasing numbers of older women becoming homeless in this country.